Two-photon excited deep-red and near-infrared emissive organic co-crystals - Yu Wang; Huang Wu; Penghao Li; Su Chen; Leighton O. Jones; Martín A. Mosquera; Long Zhang; Kang Cai; Hongliang Chen; Xiao-Yang Chen; Charlotte L. Stern; Michael R. Wasielewski; et al. (Nature Communications, 2020)
Two-photon excited near-infrared fluorescence materials have garnered considerable attention because of their superior optical properties compared with other optical materials. Here, the authors use a convenient and efficient supramolecular approach to synthesize a two-photon excited near-infrared emissive co-crystalline material.